A concerted effort to understand the ambient particulate matter in the Lower Fraser Valley: the Pacific 2001 Air Quality Study - Li, S. M. (ATMOSPHERIC ENVIRONMENT, 2004)
The Pacific 2001 Air Quality Study was a major program on ambient particulate matter carried out in the Lower Fraser Valley. This paper provides an overview of the study and gives accounts of the measurements in each major components of the field measurement program, including ground sites specifically targeted on traffic emissions, urban mixing, urban to rural transition, biogenic emissions from forest, and a mixture of urban and forest, and an airborne measurement program to link the ground based components. A summary of major findings is given in the paper, along with a general background for the papers in this issue. (C) 2004 Elsevier Ltd. All rights reserved.